The Role of the School Private Leadership in Improving Teacher’s Performance - Kurniawan, Ari; Ahyani, Nur; Fitria, Happy (Journal of Social Work and Science Education, 2024)
The study was a qualitative descriptive study that employed field observations and interviewing as data-collecting approaches. The purpose of this study was to determine how a head of school’s leadership affected teachers’ performance in 13 Koba State SD. The head of the school is a key figure in the institution, especially in terms of enacting the school’s vision and mission. Teachers have a crucial role in guiding students’ talents, interests, and skills in the advancement of science through classroom learning activities. The educational, professional, personal, and social skills of a teacher can be used to assess student achievement. The State SD 13 Koba suggests that to increase the existing human resources (SDA), through career development for teachers through training or educational seminars, since the role of the head of school has a significant impact on teacher's performance.